1993
DOI: 10.1590/s0074-02761993000100021
|View full text |Cite
|
Sign up to set email alerts
|

Use of a selective medium with potassium tellurite to follow intestinal colonization of hospitalized patients by drug-resistant Enterobacteriaceae

Abstract: Nosocomial infections are a relevant factor in complicating the recovery of patients interned for even minor causes. In a attempt to determine their origin it is crucial to consider that their origin is of an endogenous nature. Looking for an accessible expression of intestinal colonization we analyzed fecal samples from 3 separate groups of hospital patients collected after different lengths of time. For practical reasons one group was studied prospectively and two other groups (patients hospitalized for up t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0
3

Year Published

1999
1999
2013
2013

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 0 publications
0
5
0
3
Order By: Relevance
“…Selective medium were tested by culturing standard strains. Pseudomonas aeruginosa ATCC 27853 and Klebsiella pneumoniae T401F10 (a strain isolated from feces in a previous study [11], which carries a antimicrobial multiresistance plasmid) are resistant to the cephalothin concentration that we employed. Staphylococcus aureus ATCC 25923 and E. coli K12R23 (a laboratorial strain without a resistance plasmid, employed in a previous study [11]) showed susceptibility to the cephalothin concentration that was employed (32 µg/mL).…”
Section: Sample Culturementioning
confidence: 99%
See 1 more Smart Citation
“…Selective medium were tested by culturing standard strains. Pseudomonas aeruginosa ATCC 27853 and Klebsiella pneumoniae T401F10 (a strain isolated from feces in a previous study [11], which carries a antimicrobial multiresistance plasmid) are resistant to the cephalothin concentration that we employed. Staphylococcus aureus ATCC 25923 and E. coli K12R23 (a laboratorial strain without a resistance plasmid, employed in a previous study [11]) showed susceptibility to the cephalothin concentration that was employed (32 µg/mL).…”
Section: Sample Culturementioning
confidence: 99%
“…Due to great selective pressure, abusive employment of antimicrobials may cause changes in patients' microbiota and lead to consequent colonization by antimicrobial-resistant microorganisms [2,9,10]. Antimicrobial multiresistance can be observed in bacterial strains that are associated with hospital environments, both colonizing [11,12] and causing infections in hospitalized patients [1,9]. These situations emphasize the importance of studying antimicrobial resistance patterns in bacteria that are part of the microbiota in different anatomic sites.…”
mentioning
confidence: 99%
“…Obtivemos informações referentes ao peso ao nascer, à duração da permanência hospitalar, ao tipo de alimentação (aleitamento materno, artificial ou ambos) ou sua suspensão, ao tipo de parto realizado, à ocasião do rompimento de bolsa (prévia ao parto ou durante o mesmo), às patologias e complicações clínicas e à eventual utilização de antimicrobianos pelo recém-nascido. O estabelecimento do total de 30 amostras fecais de recém-nascidos teve como base a freqüência (alta) de recém-nascidos do setor apresentando cepas fecais de enterobactérias multirresistentes a antimicrobianos, em investigação anterior 12 .…”
Section: Métodosunclassified
“…É interessante considerar que quando, de fato, é essa (a microbiota materna) a determinante do processo de colonização, a imunidade passivamente adquirida confere defesas importantes para a ameaça de Neste estudo procuramos avaliar a aquisição de enterobactérias multirresistentes a antimicrobianos no intestino de recém-nascidos, empregando meios seletivos de cultura bacteriana, contendo telurito de potássio ou gentamicina. O telurito de potássio, já utilizado em investigação anterior 12 , mostrou-se menos adequado à detecção de cepas resistentes que o meio contendo gentamicina, tendose em conta que as cepas isoladas no meio contendo gentamicina apresentaram caráter de multirresistência mais marcante.…”
Section: Hupe-uerj (1991)unclassified
See 1 more Smart Citation